Routine inflammatory markers are elevated in myelodysplastic syndromes at presentation: Inflammatory marker elevation in MDS - Oster, Howard; Sklyar, Ekaterina; Golsdshmidt, Noa; Mittelman, Moshe (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Background: Immune and inflammatory processes have known contributions to the pathogenesis of myelodysplastic syndromes (MDS). The use of inflammatory markers, minimally used in current practice, is examined.